Root water transport of Helianthus annuus L. under iron oxide nanoparticle exposure - Martínez-Fernández, Domingo; Barroso, Didac; Komárek, Michael (Environmental science and pollution research international, 2016)
The application of nanomaterials in commercially available products is increasing rapidly for agriculture, phytoremediation and biotechnology. Since plants suppose the first sink for the accumulation of nanoparticles from the environment, emerging studies have focused on the general consequences for plants and their effects on the biomass production. However, effects on the root surface, as well as blockage of nutrients and water uptake by the roots, may also occur. This experiment was designed to prove if the plant water relations can be affected by the adsorption of nanoparticles on the root surface, causing a consequent stress for the plants. With this goal, plants of Helianthus annuus were previously grown in a hydroponic culture, and at age of 55 days, their roots were exposed to three different concentrations of nanomaghemite (NM) in the hydroponic solution for 5 days: control without NM; 50 and 100 mg l(-1) NM. The main effect was related to the reduction of the root hydraulic conductivity (Lo) and the nutrients uptake. The concentrations of the macronutrients Ca, K, Mg and S in the shoot were reduced relative to the control plants, which resulted in lower contents of chlorophyll pigments. Although stress was not detected in the plants, after the analysis of stress markers like the accumulation of proline or ascorbate in the tissues, reduction of the root functionality by nanoparticles has been identified here, manifested as the effect of NM on Lo. The treatment with 50 mg l(-1) NM significantly reduced the Lo, by up to 57% of its control value, and it was reduced by up to 26% at 100 mg l(-1) NM. These results will be an important factor to take into account with regard to the applicability of NM for long-term use in crops, particularly during privative water conditions.
Keywords: Ferric Compounds; Nanoparticles; chlorofyl; voda; železité sloučeniny; biologický transport; Helianthus; Biological Transport; Proline; Water; Plant Roots; biomasa; kořeny rostlin; Chlorophyll; prolin; Biomass; nanočástice